APGAR perinatal predictors persistently low at 5 minutes in a Peruvian Hospital: Predictores perinatales de APGAR persistentemente bajo a los 5 minutos en un Hospital Peruano - Chilipio Chiclla, Marco Antonio (2020)
Objective: To determine the perinatal predictors of persistently low Apgar at 5 minutes in an EsSalud hospital. Material and methods: Observational, analytical case-control study. A census analysis of 889 neonates with low Apgar (<7) at the first minute treated at the Octavio Mongrut Muñoz Hospital from 2009-2018 was carried out, after verification of the inclusion and exclusion criteria. The EsSalud Perinatal Surveillance System (SVP) was used. The Chi square test and crude odds ratio (ORc) were used as a measure of association. Likewise, binary logistic regression was applied to estimate adjusted odds ratios (ORa). Results: There were 17,780 live births during the study period, of which 889 (11.9%) had low Apgar scores at one minute. The incidence of persistently low Apgar score at five minutes was 5.68 per 1,000 live births. In the multivariate analysis, the only perinatal predictors of a persistently low Apgar score at 5 minutes were aspiration of meconium amniotic fluid (ORa = 7.82; p <0.01) and the presence of a congenital anomaly (ORa = 3.19; p <0.01). Conclusion: meconium amniotic fluid aspiration and the presence of a congenital anomaly are perinatal predictors of a persistently low Apgar score at the fifth minute of extrauterine life in an EsSalud hospital.